Fairies in Early Modern English Drama: Fictionality and Theatrical Landscapes, 1575-1615 - CULLITON, KAITLYN (Trinity College Dublin. School of English. Discipline of English, 2019)
In 1575, the fairy queen appeared as a character in the entertainments presented to Queen Elizabeth I at Woodstock in what appears to be the first instance of a fairy character scripted into an English dramatic performance. After this performance, fairies became a ubiquitous presence in English theater, appearing in nineteen extant Elizabethan and Jacobean dramatic works. Just as quickly as this character type gained popularly, however, it suddenly almost disappeared from England?s theatrical output between 1615 and the closing of the theaters in 1642. I suggest that the rise to popularity and the subsequent decline of the fairy figure in early modern English drama offers a unique opportunity to study the manner in which fairy beliefs and practices circulated and were embodied in performance spaces of early modern England. This project examines those nineteen extant English dramatic works featuring fairy characters composed between 1575 and 1615, arguing that these texts shift from portraying fictionally real fairies to fairies that are counterfeit within their respective dramatic universes. Coinciding with this development is a change in the locations in which these characters appear. In their earliest theatrical manifestations in the Elizabethan entertainments, fairies are set in the rural outdoor landscapes of the English countryside. As the depictions of fairies begin to evolve from fictionally real to counterfeit, they gradually transition into indoor spaces. I argue that the changing relationship between fairy characters and the landscapes they inhabit in dramatic texts indicates a significant historical shift toward the demythologization of the fairy figure?the process through which these figures began to be widely conceived of and written about as entities of fiction.
APPROVED
Keywords: fairies; Elizabethan and Jacobean drama; landscape